POLY(3-HYDROXYBUTYRATE)-BASED RESIN SHEET FOR HEAT MOLDING, MOLDED BODY OF SAME AND METHOD FOR PRODUCING SAME - OKURA TETSUO (2021)
A resin sheet for heat molding, which is formed of a poly(3-hydroxybutyrate)-based resin. The difference between the melting point peak temperature and the melting point peak end temperature on the high temperature side in the differential scanning calorimetric analysis of the poly(3-hydroxybutyrate)-based resin is 10 DEG C or more; and the sheet has a thickness of from 0.15 mm to 1 mm. It is preferable that the melt viscosity of the poly(3-hydroxybutyrate)-based resin at 160 DEG C is 10,000 poises or more. 本发明涉及热成型用树脂片，其包含聚(3-羟基丁酸酯)系树脂。上述聚(3-羟基丁酸酯)系树脂在差示扫描量热分析中的熔点峰温度与熔点峰的高温侧的结束温度之差为10℃以上，上述片的厚度为0.15～1mm。上述聚(3-羟基丁酸酯)系树脂在160℃下的熔融粘度优选为10000泊以上。